Perceptions of Students About the Use of Blended Learning in Computer Literacy Courses - Elmas, Mevlüt (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
The technology in our lives is changing rapidly every day. In the field of technology, our life changes after every step taken by humanity and education cannot be excluded. In addition to traditional, face-to-face education, we have different learning models today. This study was carried out in Eastern Mediterranean University, “Hukuk için Bilgisayar” (ITEC190) and “Bilgisayara Giriş” (ITEC115) courses in the 2019-2020 Spring semester. These courses were given as blended learning and students' perceptions about the use of blended learning were examined. The data were collected using a modified questionnaire prepared by Gedik (2010). Findings showed that students' perceptions about the application of blended learning were positive in these lessons. In addition, students' views on the classroom atmosphere can be positively defined. However, due to the covid-19 outbreak, students had chance to attend classes physically for only 4 weeks. As a result, some students declared that they felt lonely. As a result, some students declared that they felt lonely. Moreover, the results revealed that there was a statistically significant difference in participants' perceptions according to their gender. However, findings show that there is no significant difference between the perceptions of the participants according to the number of blended courses they have taken before.

ÖZ: Teknoloji her geçen gün hızla büyüyor. İnsanlığın teknoloji alanında attığı her adımdan sonra hayatımız değişiyor, eğitim de öyle. Geleneksel yüz yüze eğitimden, bugün farklı öğrenme modellerine sahibiz. Bu çalışma 2019-2020 Bahar döneminde Doğu Akdeniz Üniversitesi, Hukuk İçin Bilgisayar (ITEC190) ve Bilgisayara Giriş (ITEC115) derslerinde yürütülmüştür. Bu dersler karma öğrenme şeklinde verilmiştir. Bu çalışmada öğrencilerin bilgisayar okuryazarlığı derslerinde karma öğrenmenin kullanımına ilişkin algıları incelenmiştir. Bu çalışmanın araştırma sorularını incelemek için betimsel araştırma bileşenleri kullanılmıştır (Gedik, 2010). Bulgular, öğrencilerin bu derslerde harmanlanmış öğrenmenin uygulanmasına ilişkin algılarının olumlu olduğunu göstermiştir. Ayrıca, öğrencilerin sınıf atmosferi hakkındaki görüşleri verimli bir şekilde iyi olarak tanımlanabilir. Ancak, covid-19 salgını nedeniyle, öğrencilerin dönem başından kısa bir süre sonra fiziksel olarak derslere girme şansları olmadı. Bunun sonucu olarak, bazı öğrenciler kendilerini yalnız hissettiklerini beyan ettiler. Öğrenciler harmanlanmış öğrenmenin bileşenlerini kullanırken bazı teknik sorunlarla karşı karşıya kalmıştır. Ayrıca, sonuçlar katılımcıların cinsiyetlerine göre algılarında istatistiksel olarak anlamlı bir fark olduğunu ortaya koymuştur. ANOVA test bulguları, katılımcıların daha önce aldıkları harmanlanmış derslerin sayısına göre algıları arasında anlamlı bir fark olmadığını göstermektedir.
Master of Science in Information and Communication Technologies in Education. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Education, Dept. of Computer Education and Instructional Technology, 2020. Supervisor: Prof. Dr. Muhammet Yaşar Özden
Keywords: Computer Education and Instructional Technology Department; Information and Communication Technologies in Education; Blended Learning; Web-based instruction